Motivasi Ekstrinsik Mampu Meningkatkan Kinerja Karyawan (Journal of Hospital Management, 2019)
An organization must have good performance to remain in existence and excel in the competition. Performance is an indicator of the pros and cons of management decisions in decision making. A good performance can help an organization to gain profit, and vice versa if the performance falls then it can harm the organization. The purpose of this study was to determine the effect of motivation and workload on employee performance at RSIA X Cikupa with job satisfaction as an intervening variable. This type of research is quantitative research, the method used is a survey with quantitative methods through weighting at intervals. The number of samples in this study were 83 people. Data collection was carried out using a questionnaire instrument. The analysis uses multiple linear regression analysis. The results of the study are that there is a positive and significant effect between motivation and job satisfaction, there is a positive and significant effect between workload and job satisfaction, there is a positive and significant effect between job satisfaction and performance. And motivation and workload simultaneously or simultaneously have a significant effect on the performance variables at RSIA X Cikupa. The dominant variable is motivation. Keyword: Motivation, Workload, satisfaction and performance.